The effect of time of day on vestibular function and postural control - Zouabi, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
During daytime activity, individuals must run their posture, their perception of verticality and orientation in space. Few studies (Avni et al., 2006; Forsman et al., 2007) examined the effect of time of day on postural control. These studies have found contradictory results. The vestibular system is continuously involved in equilibration reaction. Only one study has tried to identify the circadian rhythmicity of the vestibular system (Wolf et al.,1990) and showed a maximum amplitude of the vestibular nystagmus in the morning. The aim of our study was to evaluate the effect of time of day on vestibular function and postural control. Methods 16 male subjects of intermediate chronotype underwent a discontinuous circadian rhythm protocol: they had one session of test per week at 2:00, 6:00, 10:00, 14:00, 18:00, 22:00 and 2:00 h. Each session consisted of 2 tests (i) static and dynamic postural control using a force platform with eyes-open and eyes-closed. The coordinates of center of pressure (COP) was recorded using a platform Posturewin® (Technoconcept, France) (ii) vestibular-ocular exploration using a rotatory chair in darkness. The stimulation used, stimulates the vestibulo-ocular reflex (VOR) and induces a vestibular nystagmus. This nystagmus can be characterized by its initial velocity (Vi) and its time constant (TC). Eye movements were recorded using an infrared video camera system Chronos® (Skalar, Nederlands). Results (i) The results of our study show that the COP was not influenced by the time of day (F=0.69, P=0.63). (ii) Vi was not influenced by the time of day (F = 0.65 P = 0.66). By contrast, the interaction of the time of day and TC was statistically significant (F=3.55, P<0.005), with a longer TC at 06:00 than 02:00h. Discussion The results of our study show that postural control in young adults is not influenced by the time of the day but that VOR duration varies during 24 hours. It is interesting to note that even if vestibular responses fluctuate during the day, postural control has no daily fluctuations. These results suggest that the vestibular variations don`t influence the postural control during the day. Compensatory mechanisms could be involved.